International trends in the incidence of testicular cancer, 1973–2002 - Chia, Victoria M. (2010)
BACKGROUND: While testicular cancer incidence rates have been widely reported in populations of Northern European ancestry, rates in other population have been less frequently examined. In a prior report, global testicular cancer incidence rates and trends for the years 1973–1997 were summarized. The current report extends these analyses with an additional 5 years of data from Cancer Incidence in Five Continents. METHODS: Age-standardized incidence rates over successive 5-year time periods were obtained for populations in the Americas, Asia, Europe, and Oceania. RESULTS: In general, testicular cancer incidence remained highest in Northern European populations (8.0–9.0 per 100,000) and lowest in Asian and African populations (<1 per 100,000). One notable exception to this pattern, however, was the very high rate reported by the Valdivia, Chile registry (8.8 per 100,000). In many populations, incidence rates rose between 1973 and 2002, although the increases were strongest and most consistent among populations of European ancestry. In some European populations, such as those of Denmark and of Geneva, Switzerland, some plateauing of rates was evident in recent years. There was little evidence of increase and possible evidence of modest decline in rates in east Asian populations. In general, the trends by histology (seminoma, nonseminoma) were similar to one another. CONCLUSIONS: Risk of testicular cancer remains high in Northern European populations and low in Asian and African populations. Reasons for increasing rates among Northern Europeans and more stable or declining rates among East Asians are unexplained, supporting the need for future etiologic studies.